2017
DOI: 10.1021/acsphotonics.7b00113
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of Strong Coupling on Nanoparticles: Revealing Absorption Anticrossing by Tuning the Dielectric Environment

Abstract: Strongly coupled plasmon-exciton systems offer promising applications in nanooptics. The classification of the coupling regime is currently debated both from experimental and theoretical perspectives. We present a method to unambiguously identify strong coupling in plasmon-exciton core-shell nanoparticles by measuring true absorption spectra of the system. We investigate the coupling of excitons in J-aggregates to the localized surface plasmon polaritons on gold nanospheres and nanorods by fine-tuning the plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
(206 reference statements)
3
32
0
Order By: Relevance
“…The particles show strong coupling or at least verge on the strong coupling regime. 19,20 The comparison between simulations and measurements for various pump powers demonstrates good agreement supporting previous studies which had to argue phenomenologically. 1.…”
supporting
confidence: 88%
“…The particles show strong coupling or at least verge on the strong coupling regime. 19,20 The comparison between simulations and measurements for various pump powers demonstrates good agreement supporting previous studies which had to argue phenomenologically. 1.…”
supporting
confidence: 88%
“…This approach has made possible the coupling of excitons with nanoparticle SPP see also the previous section, as well as of molecular vibrations with a metallic film SPP . Although quantum strong coupling has a classical analogue, the purely quantum nature of the polariton states makes them useful for quantum information processing. Several experiments demonstrated that SPP preserve quantum information and entanglement.…”
Section: Strong Coupling Applicationsmentioning
confidence: 99%
“…In this case, dark-field scattering spectroscopy is often utilized while measuring the absorption and PL 8,9 remains very challenging in contrast to ensemble measurements. 9,10 Plasmonic resonators based on nanoparticles are often regarded as nanoantennas, i.e., light concentrators or extractors. A prominent antenna effect of plasmonic particles is the enhancement of the absorption cross section of nearby dipole emitter (DE) by orders of magnitude compared to their reference value.…”
mentioning
confidence: 99%